(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
In the European context, social and emotional education (SEE) has been developed from social and emotional learning (SEL) and aims to be a core curriculum element across the region. However, to reach the current development in SEE, apart from the effort of individual nations, the roles of the European Union (EU) in uniting and strengthening the SEE concept across its member states is significant. This paper employs document analysis method as the main tool to accentuate the roles of the EU in this development process. It first identifies the educational context and policies articulated by the EU as the foundation for the induction and inception of SEE into the area, which are reviewed afterward. Finally, the current module of SEE adopted across the EU members is introduced as an illustration of the EU’s effort to bolster SEE in their regional area. This paper presents a good example of how a regional union unites and boosts their regional development in general and particularly educational innovation.